In silico Screening of Plectranthus amboinicus and Hyptis suaveolens Phytochemicals: Novel Repellents Targeting Odorant Binding Proteins of Aedes aegypti and Aedes albopictus - Jebastin, Thomas; Wilson, Jeyaraj John; Sisubalan, Natarajan; Sudhakar, Dharmarajan Raja; Sivamaruthi, Bhagavathi Sundaram; Abuthakir, Mohamed Husain Syed; Sevarkodiyone, Subramanian; Chaiyasut, Chaiyavat (Anti-Infective Agents, 2025)
Background and AimMosquitoes significantly threaten public health, transmitting dangerous diseases to humans and animals. Conventional insecticide spraying, while common, has limitations in effectively controlling vector-borne diseases. Many chemical pesticides harm humans and animals, and some persist in the environment and cause toxic effects. Recently, there has been renewed interest in plant-based products due to concerns about insecticide resistance, cross-resistance, potential toxicity associated with synthetic options, and rising costs. Therefore, this study aimed to screen the Plectranthus amboinicus and Hyptis suaveolens phytochemicals targeting the odorant binding proteins (OBPs) of Aedes aegypti and Aedes albopictus.MethodsIn this study, we conducted molecular docking analyses using specific plant-derived compounds from H. suaveolens and P. amboinicus.ResultsWe focused on the interaction of these compounds with OBPs from dengue and chikungunya vectors (Aedes aegypti and Aedes albopictus). The selected phytochemical compounds exhibited strong binding with the OBP of both Ae. aegypti and Ae. albopictus. Tetrahydrofuran-2-carboxylic acid, Carvacryl acetate, and Brallobarbital showed high binding affinity and significant interaction with Ae. aegypti. Tetrahydrofuran-2-carboxylic acid and 3-Methyl-4-isopropylphenol also demonstrated substantial binding affinity and effective interaction with Ae. albopictus OBP.ConclusionThese findings suggest that the identified compounds can potentially disrupt the attraction of mosquitoes to humans, thus reducing human-vector contact. They may offer a promising alternative for developing natural and efficient mosquito repellents, surpassing currently used synthetic options like N, N-diethyl-meta-toluamide, and other conventional repellents.
Keywords: Aedes albopictus